Transitions of Care Coordination Intervention Identifies Barriers to Discharge in Hospitalized Stroke Patients - Zimmerman, William Denney; Grenier, Rachel E.; Palka, Sydney V.; Monacci, Kelsey J.; Lantzy, Amanda K.; Leutbecker, Jacqueline A.; Geng, Xue; Denny, Mary Carter (Frontiers in Neurology, 2021)
Background: Prolonged hospital lengths of stay increase costs, delay rehabilitation, and expose acute ischemic stroke patients to hospital-acquired infections. We designed and implemented a nurse-driven transitions of care coordinator (TOCC) program to facilitate the transition of care from the acute care hospital setting to rehabilitation centers and home. Methods: This was a single-blinded, prospective, randomized pilot study of 40 participants to evaluate the feasibility of implementing a TOCC program led by a stroke nurse navigator in hospitalized acute ischemic stroke patients. The intervention consisted of a stroke nurse navigator completing eight specific tasks, including meeting with stroke patients and their families, facilitating communication between team members at multi-disciplinary rounds, assisting with referrals to rehabilitation facilities, providing stroke education, and arranging stroke clinic follow-up appointments, which were confirmed to be completed by independent study personnel. The primary outcome was to assess the feasibility of the program. The secondary outcomes included comparing hospital length of stay (LOS) and patient satisfaction between the TOCC and usual care groups. We also explored the association between patient-level variables and LOS. Results: The TOCC program was feasible with all pre-specified components completed in 84.2% (95% CI: 60.4–96.6%) and was not significantly different from the assumed completion rate of 75% (p = 0.438). There was no significant difference in median LOS between the two groups [TOCC 5.95 days (4.02, 9.57) vs. usual care 4.01 days (2.00, 10.45), false discovery rate (FDR)-adjusted p = 0.138]. There was a trend toward higher patient median satisfaction in the TOCC group [TOCC 35.00 (33.00, 35.00) vs. usual care 30 (26.00, 35.00), FDR-adjusted p = 0.1] as assessed by a questionnaire at 30 days after discharge. The TOCC study allowed us to identify patient variables (gender, insurance, stroke severity, and discharge disposition) that were significantly associated with longer hospital LOS. Conclusion: A TOCC program is feasible and can serve as a guide for future allocation of resources to facilitate transitions of care and avoid prolonged hospital stays.